Presenting the Archaeological Evidence in Aceh: International Trade Perspective - Husnia, Amir; Kabiru Rafiie, Said Achmad; Husaini, Ibrahim; Saidina, Mokhtar (School of Social Sciences, USM, 2017)
Aceh province, Indonesia. It shows that the ceramics fragment proves the connection of trade between Aceh and Southeast Asia. These specific ceramics originally come from mainland China, Thai and Vietnam. The current founding of ceramics in Malaysian Peninsula including Kedah, Melaka, and Johor confirm the similarities. It reaffirms that Aceh was the hub of international trade. This study used exploratory research approach. This approach with the narrative perspective to examine what ceramics tells us around 13th until 15th CE regarding to international trading in Lamreh, Aceh. The research will give the new perspective on historical record based on archaeological evidences. Previous researches are mainly focussing on record from international explorers. This study will help us to understand possibility to connect Aceh as part of ASEAN community to build a new international trade hub in Aceh.